2005
DOI: 10.1242/jeb.01343
|View full text |Cite
|
Sign up to set email alerts
|

Stress signaling: coregulation of hemoglobin and male sex determination through a terpenoid signaling pathway in a crustacean

Abstract: Environmental signals can activate neuro-endocrine cascades that regulate various physiological processes. In the present study, we demonstrate that two responses to environmental stress signaling in the crustacean Daphnia magna -hemoglobin accumulation and male offspring production -are co-elevated by the crustacean terpenoid hormone methyl farnesoate and several synthetic analogs. Potency of the hormones with respect to the induction of both hemoglobin and male offspring was highly correlated, suggesting tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
2
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 44 publications
3
60
2
3
Order By: Relevance
“…Transduction in the brain of the crustacean of the environmental signals into instructions (¼information) for switching to sexual reproduction involves activation of the cholinergic system in the brain (Eads et al, 2008) and causes a pulse of methyl farnesoate, which binds its specific receptor during a critical period of oocyte maturation (Rider et al 2005) (Fig. 1).…”
Section: Gene Recruitment In Transgenerational Developmental Plasticitymentioning
confidence: 99%
“…Transduction in the brain of the crustacean of the environmental signals into instructions (¼information) for switching to sexual reproduction involves activation of the cholinergic system in the brain (Eads et al, 2008) and causes a pulse of methyl farnesoate, which binds its specific receptor during a critical period of oocyte maturation (Rider et al 2005) (Fig. 1).…”
Section: Gene Recruitment In Transgenerational Developmental Plasticitymentioning
confidence: 99%
“…The insecticides pyriproxyfen, fenoxycarb and methoprene cause male broods (Tatarazako et al, 2003), with orders of magnitude greater potency than MF for pyriproxyfen and fenoxycarb. Interestingly, all of these compounds also induce Hb production in Daphnia (Rider et al, 2005). Therefore, male production and Hb induction appear to be coupled at some level by JHA signaling (see below).…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental research revealed that juvenoid hormones regulate sex determination in different arthropod groups, including cladocerans (Olmstead & LeBlanc 2002Tatarazako et al 2003;Rider et al 2005;Kim et al 2006;Oda et al 2006) and aphids (Hales & Mittler 1987, 2005. For species where males were previously unknown, a whole range of new diagnostic characters could be obtained through application of a hormone treatment (Kim et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Methylfarnesoate is a crustacean juvenoid hormone that acts through the same signalling pathway as haemoglobin induction (Rider et al 2005). The hormone induced male production in lineages that were considered as non-male producers (Rider et al 2005), and even in species for which males were not known (Kim et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation